In situ immobilization of Cal B enzyme in mesoporous materials of the MCM-48 type using different ionic solids: synthesis and application in esterification reactions - Catia Santin Zanchett Battiston; Carolina Elisa Demaman Oro; Aline M. Moreira Ficanha; Paloma Truccolo Reato; Natalia Paroul; Rogério Marcos Dallago; Marcelo Mignoni (The Journal of Engineering and Exact Sciences)
The ionic solids [C16MI]Cl and [C14MI]Cl were used as structure directors on MCM-48 mesoporous support with immobilized CALB lipase for the synthesis of esters from geraniol. Significant results were obtained in the synthesis of geranyl acetate and geranyl butyrate. Enzyme concentration, temperature and molar ratio of substrates were parameters that affect the synthesis yield. The highest temperature (60°C) and highest enzyme concentration (13%) conditions showed the best ester conversion results. For both esters, the ionic liquid [C16MI]Cl showed better conversion results and reached a value above 38% of conversion.   Furthermore, the support tested in the present study for application in ester synthesis is cost-effective. In addition, the enzymatic route to obtain the esters presents mild reaction conditions and the results show potential for application in industrial applications.